Developing an interactive scratch-based learning media to enhance students’ understanding of basic gravity concepts - Perdana, Riki; Fernandez Saragih, Januardo; Jumadi, Jumadi; Sukardiyono, Sukardiyono (WaPFi (Wahana Pendidikan Fisika), 2025)
This study aims to develop a 3D Scratch-based physics learning media to enhance student learning outcomes in basic gravity concepts. Traditional learning methods often limit student engagement and hinder the development of essential skills. By incorporating interactive simulations and animations, Scratch-based media can provide a more dynamic and engaging learning experience. The 4D development model was employed to design and develop the media, focusing on aspects such as visual clarity, accessibility, and language appropriateness. A panel of experts, comprising a physics education lecturer and three prospective physics teachers, validated the media. The results indicated that the developed media achieved a very high level of feasibility, with an average score exceeding 81%. This research suggests that the integration of Scratch-based learning media can significantly improve student learning outcomes in physics, particularly around basic gravity. The interactive nature of the media, coupled with its inclusion of exercises and discussion questions, fosters active learning and enhances comprehension.